(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Malignant hypertension is a medical emergency characterized by severe elevation in blood pressure with end-organ damage, including ocular involvement. Systemic lupus erythematosus (SLE) may result from lupus nephritis or vascular involvement in patients, and reports of severe hypertensive retinopathy in this setting are extremely limited. Herein, we report the case of a 30-year-old woman with SLE and poorly controlled chronic hypertension who presented with sudden bilateral vision loss. Ophthalmologic examination revealed grade IV hypertensive retinopathy with macular star exudates, a finding not previously described in similar reported cases. Optical coherence tomography demonstrated intraretinal hyperreflective deposits at the fovea without active macular edema, and fluorescein angiography showed areas of retinal ischemia. Intensive antihypertensive therapy and immunosuppressive treatment led to systemic stabilization but limited visual recovery. Only two similar cases have been reported, all presenting with hypertensive emergency, active SLE, and visual symptoms; however, the present case uniquely exhibited a macular star pattern. Early ophthalmologic recognition is essential for diagnosis, prognosis, and multidisciplinary management.